1000 Social Media Use And Actigraphic Measures Of Sleep Timing Among High-risk Adolescents. (27th May 2020) - Hamilton, J L; Goldstein, T R; Sewall, C; Zelazny, J; Rode, N; Gibbons, B; Franzen, P L
Abstract: Introduction: Social media use is a risk factor for poor sleep among adolescents. It remains unclear whether social media use before bed impacts later sleep timing or whether youth turn to social media because of sleep problems, which impacts sleep timing. No study to date has examined this relationship using prospective designs and objective sleep measures among high-risk adolescents, who may be particularly vulnerable to social media use. Methods: As a preliminary test of this relationship, 25 adolescents and young adults in an intensive outpatient program for depression and suicidality completed baseline measures of social media use and wore actiwatches for up to three months. Social media use included: 1) minutes of use within 2 hours of going to sleep, and 2) frequency of social media use due to difficulty falling or staying asleep. To examine social media as a predictor of sleep timing over the next month, actigraphic measures of sleep timing (i.e., onset) were used in the first month after baseline. Results: Multilevel modeling indicated that higher levels of social media use in the 2 hours before bed (mean = 46.94 minutes) predicted later sleep timing (B = .02; SE = .01; p= .003). Similarly, higher frequency of social media use due to perceived sleep problems predicted later sleep timing (B = .22; SE = .11; p= .04). Models covaried for age, gender, and prior-day depressed mood. When simultaneously entered, only minutes of social media use in the 2 hours before bed significantly predicted later sleep timing. Conclusion: Findings suggest that the relationship between social media use and sleep timing among adolescents with depression and suicidality may be driven by both social media use before bed and media use due to sleep problems. Research assessing objective social media use and daily relationships are needed to further disentangle this relationship. Support: Jessica L Hamilton is supported by a T32 fellowship from NHLBI (HL082610; PI: Buysse). This research is supported by grants from the American Foundation for Suicide Prevention and University of Pittsburgh Clinical and Translational Science Institute.